UTILIZATION OF THE PERSONNEL MANAGEMENT INFORMATION SYSTEM (SIMPEG) IN APPARATUS RESOURCE MANAGEMENT WITHIN THE SOUTH KALIMANTAN PROVINCIAL GOVERNMENT - Ade Ria Safitri; Rossy Lambelanova; Dyah Poespita Ernawati; Komaedi Komaedi (Sean Institute, 2023)
The development of information technology has an impact on several aspects of government in South Kalimantan Province by looking at ASN management which prioritizes the use of technology to serve the community more transparently, effectively and efficiently, especially in terms of easy access to information in order to realize a concept of good governance. . The gap in this research is seen from the limited use of SIMPEG in apparatus resource management. This research focuses on the South Kalimantan Regional Government, namely SIMPEG (Personnel Management Information System) as an embodiment of E-Government. SIMPEG is carried out centrally and functionally by the Provincial Civil Service Bureau/Regional Personnel Agency. In SIMPEG, it is explained that there has been no update of personnel data to help leaders carry out job mapping. The aim of this research is to examine the use of personnel management information systems in personnel resource management and inhibiting factors in SIMPEG management. Using a qualitative approach and the data is then processed based on interview data, observation and documentation through data reduction, data presentation and verification. The results of the research are that the quality of human resources is not sufficient to manage SIMPEG, the budget is not sufficient for the realization of several devices, the facilities are not ready, such as a special room for servers that does not yet exist. The SOP indicators, data maintenance, evaluation and final report are considered good so that employees are helped to utilize SIMPEG. The main obstacle in using SIMPEG as personnel resource management is that the availability of human resources in managing SIMPEG is not sufficient for application development every year so that there are still old data from each employee that is not up to date.